1998
DOI: 10.1002/(sici)1096-9071(199809)56:1<18::aid-jmv4>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

HBV core promoter mutations prevail in patients with hepatocellular carcinoma from Guangxi, China

Abstract: The development of primary liver cancer frequently is associated with persistent HBV infection, and tumours may arise in individuals who are anti-HBe positive. However, it is unclear whether viruses with an HBeAg-negative phenotype are associated with tumour development or are selected, during seroconversion, after chromosomal integration of wild-type viral DNA. In order to investigate the temporal evolution of the HBV genome in such individuals, the polymerase chain reaction was used to amplify HBV DNA from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 33 publications
7
47
1
Order By: Relevance
“…Viral replication can also be further enhanced by a second mechanism in which the transcription of the pregenomic RNA will be increased through the removal of the nuclear receptor binding site and creation of a hepatocytes nuclear binding factor 30. These changes increase the core RNA transcription with enhanced core protein, DNA polymerase, pre-genomic RNA synthesis, but suppress the precore RNA transcription whose normal function is to decrease pregenomic RNA packaging 31 32. This is in complete concordance with the finding of the present study and of Chauhan and colleagues 33.…”
Section: Discussionsupporting
confidence: 92%
“…Viral replication can also be further enhanced by a second mechanism in which the transcription of the pregenomic RNA will be increased through the removal of the nuclear receptor binding site and creation of a hepatocytes nuclear binding factor 30. These changes increase the core RNA transcription with enhanced core protein, DNA polymerase, pre-genomic RNA synthesis, but suppress the precore RNA transcription whose normal function is to decrease pregenomic RNA packaging 31 32. This is in complete concordance with the finding of the present study and of Chauhan and colleagues 33.…”
Section: Discussionsupporting
confidence: 92%
“…However this result was not statistically significant based on the Fisher exact test, 1 tail, p = 0.05, probably due to the small sample size in the groups. Other studies have shown a better correlation between the presence of T-A mutations and patients with fulminant hepatitis, severe exacerbation [20] or liver cirrhosis [22] especially with genotypes A or C when compared with asymptomatic carriers [12-14]. In agreement with the literature T-A mutations seem to appear more frequently in genotypes C [23,24] and A [13] than D [25,26] or B [27].…”
Section: Discusionsupporting
confidence: 85%
“…A double point mutation with a transversion nucleotide from adenine to thymine at nucleotide 1762, K130M with a transition from adenine to guanine at position 1764 V131I (T-A mutations), has been found more frequently in patients with hepatic tumors than in asymptomatic chronic patients from China [11,12] and Africa [13]. In East Asia where genotype C is the most common genotype, it has been reported that the T-A mutation occurs more frequently in relation to this genotype [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that these mutations were found more frequently in patients with HCC than in those with chronic hepatitis B. [61][62][63][64] Because these core promoter variants may result from a long-lasting immune response and may be associated with more severe liver disease, it is unclear if the core promoter mutations or X protein alterations are directly involved in hepatocarcinogenesis. However, a recent report suggested that they could at least be viewed as a predictor of the development of HCC.…”
Section: Mutations In X Genementioning
confidence: 99%